Identification and structural characterization of dimeric sesquiterpene lactones in Inula japonica Thunb. by high‐performance liquid chromatography/electrospray ionization with multi‐stage mass spectrometry. (2nd September 2013) - Ye, Ji; Qin, Jiang‐Jiang; Su, Juan; Lin, Shan; Huang, Ying; Jin, Hui‐Zi; Zhang, Wei‐Dong
Abstract : RATIONALE: Dimeric sesquiterpene lactones (DSLs) exhibit more 'biological friendly' and 'drug‐like' molecular features than their monomers. Identification of DSLs is important to uncover potential lead compounds for the development of new anti‐inflammatory and anticancer drugs. METHODS: High‐performance liquid chromatography coupled with electrospray mass spectrometry (HPLC/ESI‐MS n ) in positive‐ion mode was developed to analyze structurally related groups of DSLs in the species of Inula japonica Thunb. The aerial part of I. japonica was also analyzed by using HPLC‐diode‐array detection (DAD)/ESI‐MS n for the purpose of method validation. RESULTS: In positive‐ion mode, a wealth of precursor molecular ions and product ions was detected for 24 DSL standards by MS n analysis under collision‐induced dissociation. Retro‐Diels‐Alder (RDA) cleavage of the guaiane‐type SL, neutral losses of acetoxy group, CO2 and water during the MS n process yielded characteristic product ions. The chemical constituents of the crude extract of I. japonica have also been analyzed by the developed method. CONCLUSIONS: The results indicated that the developed analytical method could be employed as a rapid, effective technique for structural characterizations of DSL‐type constituents in I. japonica . This study may also arouse interest for further structural analysis of other DSL‐containing type herbal medicines. Copyright © 2013 John Wiley & Sons, Ltd.